Intelligent Network Temperature and Humidity Measuring System Based on USB Interface - Zhiguo Huang; Zhixin Huang; Xihe Cui; Shengli Han (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Multi digital output relative humidity and temperature sensors-SHT71 were set network monitoring points in the system, which can measure at any moment, timing, real-time temperature and relative humidity per point of the environment by-turn. Temperature-humidity value, dew-point value, date and time per point were displayed by lattice graphics LCM (Liquid Crystal Display Module) HY-12864K. At the same time, they were saved in nonvolatile FRAM (Ferroelectric Random Access Memory) FM31256, which can assure data do not lose after the power of the system fail. Acquired data can be uploaded directly to PC in the USB-HOST mode or be copied indirectly to PC far away from testing field by flash disk in the USB-DEVICE mode. The application software not only can draw temperature, humidity and dew-point curve and calculate maximum, minimum, average, but also can make further statistical analysis, report forms printing and set-up basic measure parameters of the system. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5114